Synthesis of A New Thiadiazole-Benzodioxole Derivative, Investigation of Acetylcholinesterase Inhibition with In Vitro and In Silico Studies - Göktaş, Sare Peçe; Osmaniye, Derya; Levent, Serkan; Özkan, Begüm Nurpelin Sağlık; Göktaş, Bünyamin; Uslu, Harun; Özkay, Yusuf (Anadolu Üniversitesi, 2024)
Alzheimer’s disease is a progressive and degenerative brain disease that negatively affects people’s lives and reduces cognitive and sensory human functions. Today, there are active ingredients that work on Alzheimer’s disease, containing benzodioxole and thiadiazole rings. Acetylcholinesterase terminates neurotransmission in the nervous system and leads to the accumulation of acetylcholine, overstimulation of various receptors and consequent impairment of neurotransmission. Thiadiazole and benzodioxole rings are compounds that exhibit a wide range of biological activities, especially known to be effective on acetylcholinesterase. A new compound containing benzodioxole and thiadiazole rings was designed, synthesized and its chemical structure was revealed using spectroscopic methods such as HRMS, 13C-NMR and 1H-NMR. Acetylcholinesterase inhibition activities were investigated using in vitro methods. To elucidate the acetylcholinesterase inhibition of compound 4a, it was subjected to in silico insertion procedure with 4EY7. Compound 4a exhibited 0.114±0.005 µM against AChE. The above data is compared with data for donepezil (0.0201±0.0014 µM), the reference compound in our study.
Keywords: Pharmacology and Pharmaceutical Sciences (Other); Eczacılık ve İlaç Bilimleri (Diğer)